Governance alternatives for local development. Government-society co-responsibility for community improvement in Mexico - Santes-Álvarez, Ricardo V. (Iberoamerican Journal of Development Studies, 2023)
The feasibility of co-responsible governance as an option to achieve better stages of development is examined in the context of a local government and a community, in north-western Mexico. For this, a qualitative analysis of a project for the strengthening of social cohesion, promoted by members of four colonies in response to a contest launched by the municipality, is carried out. The results indicate that the exercise of power maintains the inertia of conventional style in the government-society interaction, where decision-making is centralized, exclusionist and opaque. Likewise, that despite advances in the project’s objectives, uncertainties about its fate caused lack of coordination within community members. In the paper, it is concluded that aiming at local development which embraces a governance style of shared responsibilities for authorities and citizens there is the need of institutional reforms. Reforms must encourage decentralization, inclusion and transparency in decision-making, within a framework of broad dialogue and agreement.